Five Linguistic Methods for Revitalizing Indigenous Laws - Metallic, Naiomi (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2023)
Building on the ground-breaking work on the revitalization of Indigenous laws ongoing over the past decade, this article seeks to contribute to our understanding of how Indigenous languages can be used to recover Indigenous laws. It posits that there is not one single linguistic method, but at least five: 1) the ‘Meta-principle’ method; 2) the ‘Grammar as revealing worldview’ method; 3) the ‘Word-part’ method; 4) the ‘Word-clusters’ method; and 5) the ‘Place names’ method. Using the Mìgmaq language to illustrate, the article explains each method and provides examples of how they can be used to inform Indigenous law revitalization. The article also shows that one does not have to be a fluent, first-language speaker to engage with linguistic methods for Indigenous law revitalization, by highlighting the various published resources like dictionaries and lexicons, reference and teaching texts, atlases, and more, that can be harnessed to engage in this work. This makes engaging with the linguistic methods accessible to the many Indigenous peoples who, because of the impacts of colonialism, are only starting to re-learn their Indigenous language. This revelation should give greater confidence to the non-fluent that they too can play a role in the revitalization of both their language and laws.